1994
DOI: 10.1287/moor.19.1.53
|View full text |Cite
|
Sign up to set email alerts
|

An O(√nL)-Iteration Homogeneous and Self-Dual Linear Programming Algorithm

Abstract: We present an O(√nL)-iteration homogeneous and self-dual linear programming (LP) algorithm. The algorithm possesses the following features: • It solves the linear programming problem without any regularity assumption concerning the existence of optimal, feasible, or interior feasible solutions. • It can start at any positive primal-dual pair, feasible or infeasible, near the central ray of the positive orthant (cone), and it does not use any big M penalty parameter or lower bound. • Each iteration solves a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
217
0
2

Year Published

1996
1996
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 320 publications
(219 citation statements)
references
References 23 publications
0
217
0
2
Order By: Relevance
“…Nesterov and Nemirovsky proved that a polynomial-time barrier method can be constructed for any CP that meets certain technical conditions [117]. Other authors have shown that problems which do not meet those conditions can be embedded into larger problems that doeffectively making barrier methods universal [169,102,1711.…”
Section: Theoretical Propertiesmentioning
confidence: 99%
“…Nesterov and Nemirovsky proved that a polynomial-time barrier method can be constructed for any CP that meets certain technical conditions [117]. Other authors have shown that problems which do not meet those conditions can be embedded into larger problems that doeffectively making barrier methods universal [169,102,1711.…”
Section: Theoretical Propertiesmentioning
confidence: 99%
“…From the optimal solution of the larger problem one can recover an optimal solution of the original problem, or detect infeasibility [7][8][9][10][11][12];…”
Section: Initializationmentioning
confidence: 99%
“…In 1994, Ye, Todd and Mizuno [21] introduced the so-called homogeneous self-dual embedding technique to solve linear programs. The main feature of this technique is to construct an artificial problem by embedding a primal-dual problem pair.…”
Section: Introductionmentioning
confidence: 99%